1978
DOI: 10.1016/0309-1651(78)90093-0
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules in mouse embryo fibro blasts extracted with Triton X-100

Abstract: Treatment of mouse embryo fibroblasts with 1% Triton X-100 at 37 degrees C in the presence of 4M glycerol and 1 mM EGTA results in the extraction of about 80% cellular proteins. Indirect immunofluorescent staining with monospecific antibodies against tubulin showed that extracted cultures contained a well developed system of cytoplasmic microtubules, indistinguishable from a system of control non-extracted cells. Microtubules in extracted cells were sensitive to Ca2+ ions, and to cold or prolonged incubation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…This method preserves microtubule and microfilament networks (Bershadsky et al, 1978). As observed by scanning electron microscopy, the cytoskeleton was well-developed in control ( Fig.…”
Section: Analysis Of the Cytoskeletal Network In Ifn-treated Y-1 Cellmentioning
confidence: 78%
See 1 more Smart Citation
“…This method preserves microtubule and microfilament networks (Bershadsky et al, 1978). As observed by scanning electron microscopy, the cytoskeleton was well-developed in control ( Fig.…”
Section: Analysis Of the Cytoskeletal Network In Ifn-treated Y-1 Cellmentioning
confidence: 78%
“…(105) were grown for 24 h on glass coverslips in culture dishes. After 24 h treatment with either IFN, cholera toxin or serum-free medium, the cells were washed and extracted for 5 min at 37 °C with 1% Triton X-100 (Bershadsky et al, 1978). Glutaraldehyde-fixed (1%) cells were dehydrated in graded ethanol series and then acetone, dried using a CO2 critical point method (Balzer CPD 010) and coated with 10 nm-thick Au-Pd by sputtering (Balzer SCD 020).…”
Section: Methodsmentioning
confidence: 99%
“…From the electron microscopic observations of epoxyembedded sections, the filaments resistant to the extraction by 1% Triton X-100 were thought to represent MFs, MTs and IFs, and those resistant to the extraction by 1% Triton X-100 and 0.3 M KI were thought to represent IFs. Bershadsky et al (1978) reported that the treatment of cultured cells with 1% Triton X-100 resulted in the extraction of about 80% cellular protein, and according to Blikstad et al (1978), high proportion of the released actin is likely to be of an unpolymerized form. So it seems unlikely that treatment with 1% Triton X-100 at 3TC in the presence of 4 M glycerol and 0.1 mM EDTA affects the structure of the hepatocyte cytoskeletons.…”
Section: Electron Microscopy Of Epoxy-embedded Sectionsmentioning
confidence: 99%
“…For indirect-immunofluorescence staining, cultures were extracted with buffered 1% Triton X-100 and fixed with formaldehyde. Details of the procedures were described earlier (13,14). The following first-step antibodies were used: rabbit antibodies to actin, Abbreviations: PEG, polyethylene glycol.…”
Section: Introductionmentioning
confidence: 99%
“…§1734 solely to indicate this fact. tubulin, and fibronectin, which were described earlier (13)(14)(15), and S47D9 monoclonal antibody, reacting with vimentin and prekeratin (16 Fig. 1 i, j, and k. Focal contacts were visualized by a novel antibody-exclusion method, giving better contrast than usual interferencereflection microscopy (17).…”
mentioning
confidence: 99%